2020
DOI: 10.1080/03057925.2020.1765740
|View full text |Cite
|
Sign up to set email alerts
|

‘You have to change, the curriculum stays the same’: decoloniality and curricular justice in South African higher education

Abstract: This paper reports on a study that focuses on students from rural areas of South Africa and their experiences of higher education. These students have attracted little attention in widening participation research in South Africa, despite being one of the most marginalised groups (Mgqwashu 2016a). The paper, drawing on the experiences of student co-researchers and using the concepts of decoloniality and curricular justice as a theoretical framework, argues for greater acknowledgement of epistemic reciprocity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The need for transformation in South African universities was foregrounded by student protests, beginning with the #RhodesMustFall movement in 2015-2016, which lead to major upheaval in the university system. These protests called for decolonisation of curricula that they argued were framed with reference to race and social class (Naidoo, et al, 2020). Research conducted by the University of Cape Town working group set up in 2016 after the protests revealed that curriculum content at the University of Cape Town was still imbued with colonialism.…”
Section: Contextualising South African Hementioning
confidence: 99%
See 1 more Smart Citation
“…The need for transformation in South African universities was foregrounded by student protests, beginning with the #RhodesMustFall movement in 2015-2016, which lead to major upheaval in the university system. These protests called for decolonisation of curricula that they argued were framed with reference to race and social class (Naidoo, et al, 2020). Research conducted by the University of Cape Town working group set up in 2016 after the protests revealed that curriculum content at the University of Cape Town was still imbued with colonialism.…”
Section: Contextualising South African Hementioning
confidence: 99%
“…Other scholars such as Kanbur and Venable (2005) have provided seminal accounts by compiling empirical evidence on spatial inequalities in more than fifty developing countries. In recent years, a volume of research in South Africa has attempted to understand the complexities of the problems of rural communities and schooling (see Naidoo, et al, 2020;Timmis, et al, 2019;Walker & Mathebula, 2019;Walker, 2019). Given the attention to spatial inequalities in the scholarly literature, rurality may be an important stratifier of educational outcomes that requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Also writing from a South African context, Naidoo et al (2020) While decolonization meant recognizing constraints, disrupting, and/or accommodating alternatives, how the latter manifested varied depending on context. Furthermore, actualizing DCP took four forms: (a) probing the positionality of knowledge, (b) constructing an inclusive curriculum, (c) relational teaching and learning, or (d) bridging higher education institutions with community and/or sociopolitical movements.…”
Section: Application and Practicementioning
confidence: 99%
“…Previous studies on decolonising higher education (Naidoo, Traher, Lucas, Muhuro & Wisker, 2020;Zembylas, 2018) have generally focused on transforming university curricula to reflect the diversity of current student populations. However, few studies have investigated the socio-economic conditions of coloniality that continue to affect previously disadvantaged students.…”
Section: Decoloniality and South African Higher Educationmentioning
confidence: 99%
“…In a study of rural students' experiences of the curriculum in South Africa, Naidoo et al (2020) found that students from rural communities continue to experience epistemic exclusion, because universities disregard the realities of their socioeconomic contexts. The neoliberal university is insensitive to the socio-economic realities of poor students, because it is entangled in a neoliberal framework that sustains coloniality.…”
Section: Decoloniality and South African Higher Educationmentioning
confidence: 99%